Politics of Revenue Allocation in Nigeria: a re-Visitation - Ikeji, Chibueze C. (Richtmann Publishing, 2011)
Revenue sharing or allocation in federal political system is prone to a number of problems rooted in politics. Federalizedsystem essentially places emphasis on cooperation and compromise. Revenue allocation in a federal system is one such area that call for agreat deal of consensus built on meaningful compromises. Of the many problem that have always arisen with regard to revenue sharing inall federations, two stand out with respect to Nigeria. The first is how to deal with the problems arising from inequalities in size andwealth among federating units. The second is how to ensure that growth of any unit does not suffer because some other unit(s) showsinability to catch up with the more progressive one(s). These problems have been variously tackled in Nigeria through the instrument offiscal review Commissions. These Commissions had operated under very charged atmospheres given the highly emotive and volatile natureof the politics of revenue allocation. The nature and outcome of the efforts of these Commissions remain ad hoc arising questions over theirutility in dealing with the ever-controversial and polemical issue of revenue allocation. This paper is an attempt at an inquiring into theforces at work in the politics of revenue sharing in Nigeria. Have the various formulas served the purpose of ensuring equitable fiscalfederalism? It is argued in this paper that the dream of equitable and acceptable revenue sharing in Nigeria is yet to be realized, and willremain far-fetched as long as political calculations govern the choice of formula to the virtual exclusion of sound economic and publicfinance practice based on optimal allocation efficiency and distributive equity.